Unraveling the Key Relationship Between Perovskite Capacitive Memory, Long Timescale Cooperative Relaxation Phenomena, and Anomalous J–V Hysteresis. Issue 4 (6th April 2021) - Hernández-Balaguera, Enrique; del Pozo, Gonzalo; Arredondo, Belén; Romero, Beatriz; Pereyra, Carlos; Xie, Haibing; Lira-Cantú, Mónica
Abstract : Perovskite Solar Cells In article number 2000707, Enrique Hernández‐Balaguera and co‐workers explored the inherent characteristic phenomenology of perovskite solar cells, in terms of anomalous ionic and electronic dynamics, long‐memory effects, and anomalous hysteresis, using electrical analysis strategies and fractional calculus tools. Thus, this work can help to advance in the understanding of the key attributes and unique physical mechanisms of photovoltaic perovskites at long time scales.